PENGGUNAAN KALIMAT TIDAK EFEKTIF PADA PENYUSUNAN NASKAH SOAL BUATAN GURU - Kodrat Eko Putro Setiawan, dan Devi Cintia Kasimbara, Wahyuningsih, (Sasando, 2020)
The teacher's ability to compile a test script using effective sentences is still very concerning. It is known from the texts compiled by many teachers of SMKN 2 Ngawi that do not have a clear subject or predicate, many word choices are wrong, as well as the use of spelling. Therefore, this study focused on the use of ineffective sentences, especially in terms of equivalence, efficiency, accuracy, and spelling. The method in this research is descriptive qualitative. Sources of data are samples of summative questions in SMKN 2 Ngawi, similar research and relevant literature. The technique of data analysis is through reading a sample text summative questions, marking sentences that contain ineffective sentences based on the characteristics of effective sentences, classifying the ineffectiveness of sentences based on the aspects analyzed, calculating the number of errors, concluding aspects of errors and compiling a synthesis of the analyzed data by interpreting them. The results of this study found that 379 sentences were ineffective, consisting of 25.6% error in equivalence, 12.1% savings, 18.2% accuracy and 44.1% spelling.